Supporting the poor to access sanitation: key lessons from targeted household consumer subsidies in Cambodia. Issue 6 (18th August 2022) - Kohlitz, Jeremy; Lala, Sunetra; Bartell, Janita; Halcrow, Gabrielle; Foster, Tim; Willetts, Juliet
ABSTRACT: This paper presents the experiences of two household sanitation subsidy initiatives piloted by SNV and WaterSHED targeting poor households in rural Cambodia. Each initiative offered eligible households a subsidy to help manage the upfront costs of constructing new pour-flush latrines. Subsidy uptake by households was limited by affordability of the required household contribution, insufficient time for households to mobilise funds, and unavailability of land. However, when taken up, the subsidies also often mobilised significant household investment. Overall, these experiences point to the need to understand how poor households respond to subsidy opportunities and to adapt subsidy mechanisms accordingly.